Matrix glycoconjugate characterization in multispecies biofilms and bioaggregates from the environment by means of fluorescently-labeled lectins - Neu, Thomas R.; Kuhlicke, Ute (Frontiers in Microbiology, 2022)
Environmental biofilms represent a complex mixture of different microorganisms. Their identity is usually analysed by means of nucleic acid based techniques. However, these biofilms are also composed of a highly complex extracellular matrix produced by the microbes within a particular biofilm system. The biochemical identity of this extracellular matrix remains in many cases an intractable part of biofilms and bio-aggregates. Consequently, there is a need for having an approach that will give access to the fully hydrated structure of the extracellular matrix or at least a major part of it. A crucial compound of the matrix identified as carbohydrate based polymers represent a major structural and functional constituent. These glycoconjugates can be characterised by using fluorescently labelled lectins in combination with confocal laser scanning microscopy. The lectin approach defined previously, as fluorescence lectin-barcoding (FLBC) and fluorescence lectin-binding analysis (FLBA) were FLBC is equal to the screening of a particular sample with all commercially available lectins and FLBA is the actual analysis of the matrix throughout an experiment with a selected panel of lectins. As the application of immune based techniques in environmental biofilm systems is impossible, the lectin approach is currently the only option for probing lectin-specific glycoconjugates in complex biofilms and bio-aggregates. From all commercially available lectins tested, the lectins AAL, HAA, WGA, ConA, IAA, HPA and LEA showed the highest binding efficiency. Furthermore, 20 of the overall lectins tested showed an intermediate signal intensity, nevertheless very useful for assessment of matrix glycoconjugates. With the data compiled, we shall virtually shed more light into the dark matter of the extracellular matrix and their 3-dimensional distribution in environmental biofilm systems. The results will be helpful in future studies with focus on the extracellular matrix glycoconjugates present in environmental microbial communities.